Brewery by-products (yeast and spent grain) as protein sources in rainbow trout (Oncorhynchus mykiss) feeds - Estévez, Alicia; Padrell, Lluis; Iñarra, Bruno; Orive, Mikel; San Martin, David (Frontiers in Marine Science, 2022)
A trial was conducted to analyze the effect of the inclusion of yeast and spent grain obtained from breweries in feeds for rainbow trout (Oncorhynchus mykiss), taking into account the availability of these by-products, produced in large quantities in Europe. The ingredients were assayed in both dried and hydrolyzed format and compared with a commercial dried or hydrolyzed yeast. According to the results, the inclusion of 20% yeast and 15% spent grain in the feed, formulated with only 15% inclusion of fish meal, produced similar results in growth among all the groups, a food conversion significantly lower for the control and spent grain formulated feeds, and rainbow trout muscle composition similar to the fish fed with a control commercial feed and showed a protein digestibility of 87%–89% without differences with the commercial yeast. Hydrolysis of the ingredients had no effects on the protein digestibility of the feeds. Protein digestibility of the ingredients was lower for spent grain. An inclusion rate not higher than 15% for spent grain is recommended. These industrial by-products can be a good source to reduce the use of plant-based ingredients and increase the sustainability of both sectors, brewery industry, and aquaculture.